To what extent are patients' needs met on oncology units? The phenomenon of care rationing - Papastavrou, Evridiki; Charalambous, Andreas; Vryonides, Stavros; Eleftheriou, Christos; Merkouris, Anastasios (My University, 2016)
Evidence suggests that when resources are not sufficient to provide all the care needed by their patients, nurses are forced to ration their attention between care activities. The aim of this study is to examine care omissions and their causes in oncology units.
Keywords: Care rationing; Missed care; Oncology units; Patient safety